Istilah-Istilah dalam Tradisi Reresik Sendhang di Desa Wonosoco Kecamatan Undaan Kabupaten Kudus (Suatu Kajian Etnolinguistik) - Janah, Miftahul; M.Pd., Widodo; Astuti, Eka Yuli (Sutasoma : Jurnal Sastra Jawa, 2019)
Reresik sendhang tradition is one of social culture in Wonosoco village which is conserved until today. This tradition has a special uniqueness compared with the other place, it has seven steps of tradition ritual and Wayang Klitik exhibition played by a Dalang from one generation. Reresik sendhang is not only a tradition, but also related with the social life and a legend of Wonosoco village. Besides that, that traditions also has some purposes and functions which are contained in the terminology. The data collections in this research used an observation and talking with advanced technique, those are interview, inducement, record, and note. The data analysis methods in this research are distributional and padan methods. The results of this research are (1) the terminology contained in Reresik sendhang tradition organized by words and phrases. (2) the terminology in Reresik sendhang tradition has lexical and cultural meaning. (3) the terminology in Reresik sendhang tradition has some functions, those are as the homage to the ancerstors, as the gratitude, cultural conservation, depict share-work attitude, water conservation, and the entertainment medium. Key words: Reresik sendhang tradition, terminology, meaning